Evaluation of the compatibility of clinical primary diagnoses with mri reports in patients with temporomandibular disc displacement (Annals of Medical Research, 2021)
Aim: Temporomandibular joint disorder (TMD) is a common disease group in the community that includes chewing muscles and temporomandibular joint (TMJ) components. TMJ diseases are also the main cause of non-odontogenic pain of the orofacial region. The aim of this study is to evaluate the consistency between clinical diagnosis and Magnetic Resonance Imaging (MRI) reports in patients with reduction with disc displacement (DDWR) and reduction without disc displacement (DDWoR).Materials and Methods: A total of 62 TMJ anamnesis records and MRI results were evaluated by authors. Radiology reports and anamnesis records were divided into two groups according to the clinical primary diagnosis file as DDWR and DDWoR. The clinical and radiographic results were compared each other and the correlation between these results was evaluated statistically.Results: The study includes sixty-two patients’ MRI reports and TMJ clinical anamnesis files (12 males and 50 female) with a mean age of 31.20±13.66 years. In group DDWoR there is only 41.9 % and in group DDWR there is only 45.2 % correlation found between clinical and MRI reports of the patients. Although the values obtained are statistically significant, there is insignificant agreement between in the TMJ clinical anamnesis file and MRI report results. There is no statistically significant difference between primary clinical diagnosis groups in terms of clinical and MRI diagnosis compatibility.Conclusion: It is concluded that clinical findings determined by the clinicians do not compatible MRI reports determined by radiologist. This may be due to the subjective nature of the clinical findings, and both MRI and clinical results are needed for precise results.
Keywords: Internal derangement; magnetic resonance imaging; temporomandibular joint